2019
DOI: 10.1186/s12886-019-1100-7
|View full text |Cite
|
Sign up to set email alerts
|

LASIK-induced corneal changes after correction of hyperopia with and without application of Mitomycin-C

Abstract: Background The study aimed to assess the role of intraoperative mitomycin-C (MMC) application during hyperopic LASIK correction (+ 1.00 D to + 6.00 D) by examining topographic corneal changes and incidence of regression over a one-year follow-up period. Methods This comparative randomized control study included 68 hyperopic patients (136 eyes) divided into two groups; Group A included 34 patients (68 eyes) that had LASIK with the application of 0.02% MMC for 10 s on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
4
0
2
Order By: Relevance
“…Topographic stability over one-year follow-up was documented in our study similar to Moawad et al [ 41 ] who reported fewer topographic changes after mitomycin C assisted hyperopic LASIK. Gauthier-Fournet et al [ 42 ] evaluated the effect of postoperative keratometry on the safety of LASIK for high hyperopia up to 9.5 D and found that corneas with steeper postoperative keratometries were associated with higher loss of CDVA.…”
Section: Discussionsupporting
confidence: 89%
“…Topographic stability over one-year follow-up was documented in our study similar to Moawad et al [ 41 ] who reported fewer topographic changes after mitomycin C assisted hyperopic LASIK. Gauthier-Fournet et al [ 42 ] evaluated the effect of postoperative keratometry on the safety of LASIK for high hyperopia up to 9.5 D and found that corneas with steeper postoperative keratometries were associated with higher loss of CDVA.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies for LASIK or conventional PRK in hyperopia removal had used smaller optical zones, which might have resulted in unpredictable post-operative vision and higher regression. 33 , 35 , 39 , 40 The sudden transition area from ablated to unablated surface, leading to uncontrolled tissue regeneration, is thought to cause such unpredictability.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the ablation zone 6 and application of 0.02% mitomycin C may help reduce the risk of regression and scarring. 13 …”
Section: Discussionmentioning
confidence: 99%